Mitochondrial DNA in Tumor Initiation, Progression, and Metastasis: Role of Horizontal mtDNA Transfer - Berridge, Michael V; Dong, Lanfeng; Neuzil, Jiri (Cancer research, 2015)
Mitochondrial DNA (mtDNA), encoding 13 out of more than 1,000 proteins of the mitochondrial proteome, is of paramount importance for the bioenergetic machinery of oxidative phosphorylation that is required for tumor initiation, propagation, and metastasis. In stark contrast to the widely held view that mitochondria and mtDNA are retained and propagated within somatic cells of higher organisms, recent in vitro and in vivo evidence demonstrates that mitochondria move between mammalian cells. This is particularly evident in cancer where defective mitochondrial respiration can be restored and tumor-forming ability regained by mitochondrial acquisition. This paradigm shift in cancer cell biology and mitochondrial genetics, concerning mitochondrial movement between cells to meet bioenergetic needs, not only adds another layer of plasticity to the armory of cancer cells to correct damaged mitochondria, but also points to potentially new therapeutic approaches.
Keywords: nádory; metastázy nádorů; Humans; Mitochondria; Mutation; mitochondriální DNA; DNA, Mitochondrial; zvířata; Genetic Techniques; genetické techniky; mitochondrie; Disease Progression; Neoplasm Metastasis; Animals; lidé; progrese nemoci; Neoplasms; mutace; technika přenosu genů; Gene Transfer Techniques